Triple negative breast cancer - Ovčariček, Tanja (Radiology and oncology (Ljubljana), 2011)
Background. Triple negative breast cancer (TNBC) is defined by a lack of expression of both estrogen (ER) and progesteron(PgR) receptors as well as human epidermal growth factor receptor 2 (HER2). Our retrospective analysis addressed prognostic factors for short- and long-term outcomes of patients (pts) with TNBC pts treated in routine clinical practice. Patient and methods.Our retrospective study included 269 TNBC treated at Institute of Oncology Ljubljana between March 2000 and December 2006. The collected data included patientsć, tumoursć and treatmentsć characteristics. The survival analyses were performed using the Kaplan-Meier method. The Cox proportional hazard model was used in the multivariate analysis. Results. The median age ofour patients was 55.3 yrs (23-88.5) and the median follow-up was 5.9 yrs (0.3-9.6). Six (2%) pts experienced local only, 79 (92%) pts distal recurrenceand 66 (24%) died. The predominant localisation of the first relapsewas in visceral organs (70.4%). The 5-year disease-free survival (DFS) for the entire group was 68.2% and the 5-year overall survival (OS) was 74.5%.We found a pattern of high recurrence rate in the first 3 years following the diagnosis and a clear decline in recurrence rate over the next 3years. In the univariate analysis age, nodal status, size and lymphovascular invasion (LVI) were found to have a significant impact on DFS as well as on OS. In the multivariate analysis only age (HR=1.79; 95%CI=1.14-2.82; p=0.012) and nodal status (HR=2.71; 95%CI=1.64-4.46; p<0.001) retained their independent prognostic value for DFS and for OS only the nodal status (HR=2.96; 95%CI=1.51-5.82; p=0.002). (Abstract truncated at 2000 characters)
Keywords: breast; dojke; napovedni dejavniki; neoplasm; prognoza; rak (medicina); therapy; tumor; zdravljenje